Pengaruh Pupuk Cair Limbah Biogas pada Tanaman Selada (Lactuca sativa L) - Saufani, Imam; Wawan, Wawan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This study aims to determine the dosage of biogas waste liquid fertilizer that produces growth and yield of lettuce (Lactuca sativa L) best. The research was conducted in Experimental Field of Faculty of Agriculture, University of Riau. The soil type used is Inceptisol. The study was conducted for three months starting from May to July 2016. The experiment was conducted experiments using Completely Randomized Design (RAL), which consisted of 6 treatments and 4 replications. The total experimental unit was 24 plots, with each plot contained 9 plants. Each plot was taken 3 randomly sampled plants. The observational data were analyzed statistically using Analysis of Varian (ANOVA), and  Duncan Multiple Range Test at the 5 % level. The observed parameters consist of plant height, leaf number, fresh weight of plant, fresh weight of plant worth consumption and dry weight of the plant. The results showed that the treatment of biogas waste liquid fertilizer can increase the height of the plant, the number of leaves, the fresh weight of the plant / plot, the fresh weight of the plant is feasible consumption / plot and dry weight. The best treatment for lettuce production was the application of liquid biogas waste fertilizer with a dose of 3.5 liters / plot.  Keywords: waste biogas, liquid fertilizer, lettuce